2019
DOI: 10.1038/s41398-019-0379-8
|View full text |Cite
|
Sign up to set email alerts
|

Key role of gut microbiota in anhedonia-like phenotype in rodents with neuropathic pain

Abstract: Patients with chronic neuropathic pain frequently suffer from symptoms of anhedonia, which is a core symptom of depression. Accumulating studies suggest that gut microbiota may play a role in depression via gut–microbiota–brain axis. However, it is unknown whether gut microbiota plays a role in neuropathic pain-associated anhedonia. Here, we used a rat model of spared nerve injury (SNI). Hierarchical cluster analysis of sucrose preference test (SPT) results was used to classify the SNI rats with or without anh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 41 publications
7
118
0
1
Order By: Relevance
“…One study (Yang C. et al, 2019) observed an increased pain-like phenotype in antibiotic-treated mice. Furthermore, mice that received antibiotics and FMT with feces from a neuropathic pain rat model with anhedonia-like phenotype developed more pain-symptoms compared to antibiotic-and PBS-treated mice.…”
Section: Fmt Studies In Animal Models (Table 5)mentioning
confidence: 99%
“…One study (Yang C. et al, 2019) observed an increased pain-like phenotype in antibiotic-treated mice. Furthermore, mice that received antibiotics and FMT with feces from a neuropathic pain rat model with anhedonia-like phenotype developed more pain-symptoms compared to antibiotic-and PBS-treated mice.…”
Section: Fmt Studies In Animal Models (Table 5)mentioning
confidence: 99%
“…Multiple lines of evidence suggest that gut microbiota might be involved in the pathophysiology of depression and in the antidepressant‐like effects of certain potential candidates . Recently, we investigated the possible role of gut microbiota in the antidepressant effects of ( R )‐ketamine in CSDS‐susceptible mice.…”
Section: Molecular and Cellular Mechanisms Of Ketamine’s Antidepressamentioning
confidence: 99%
“…Gut microbiota is an important modulator of neuropsychiatric disorders and has been demonstrated to be closely associated with depressive‐like behaviors in rodents with stress or neuropathic pain 36,37 . However, whether gut microbiota involves in EAP‐induced depressive‐like behaviors in mice remains undetermined.…”
Section: Discussionmentioning
confidence: 99%